2018
DOI: 10.1007/s00192-018-3745-9
|View full text |Cite
|
Sign up to set email alerts
|

New approach to the evaluation of perineal measurements to predict the likelihood of the need for an episiotomy

Abstract: This study introduces measures of AGD as risk factors for episiotomy. We propose that "gh + pb" length <77 mm and AGDac <93 mm may predict the likelihood of requiring episiotomy and may be useful for diminishing subjectivity in the decision to perform an episiotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…All investigations identified a lower incidence of episiotomies if perineal massage was applied. It should be emphasized that the decision to perform episiotomy is made by the healthcare team attending the delivery, based on professional judgment guided by experience, training, and decision‐making capacity in relation to possible complications 30 . Such an intervention is usually performed to prevent perineal tears or, if they do occur, to reduce their severity 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All investigations identified a lower incidence of episiotomies if perineal massage was applied. It should be emphasized that the decision to perform episiotomy is made by the healthcare team attending the delivery, based on professional judgment guided by experience, training, and decision‐making capacity in relation to possible complications 30 . Such an intervention is usually performed to prevent perineal tears or, if they do occur, to reduce their severity 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the decision to perform episiotomy is made by the healthcare team attending the delivery, based on professional judgment guided by experience, training, and decision-making capacity in relation to possible complications. 30 Such an intervention is usually performed to prevent perineal tears or, if they do occur, to reduce their severity. 31,32 Evidence to date has shown that routine episiotomies do not reduce perineal trauma and that a protocol to reduce episiotomies is safer for mother and baby.…”
Section: Discussionmentioning
confidence: 99%
“…Favoring the discussion about the importance of these outcomes, a cohort [34] that analyzed 57.267 deliveries concluded that a maternal pushing more than 30 minutes long during the second stage of labor, and an expulsive stage more than one hour long are the potential factors for maternal and neonatal morbidities, especially postpartum hemorrhage, as well as uterine atony and cervical and perineal lacerations. This study recommends caution regarding obstetric interventions and better analyzing expectant management during the second stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing research on pain, anxiety, and maternal fatigue in the second period of labor there is no consistent evidence about a direct association with the type of pushing. It is understood, however, that those outcomes might influence labor progression, as the stress generated by these sensations result in a greater release of catecholamines, fatty acids, and lactate, which can reduce the effectiveness of uterine contractions, possibly leading to prolonged labor, and consequently to dystocia, instrumentalization, higher post-partum hemorrhage risk, fetal distress and negative labor experience for the woman [32,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Perineal sizes were perineum body (PB): the distance between the posterior margin of the genital hiatus and the middle part of the anus at the time of exertion; genital hiatus (GH): the distance between meatus urethra to the posterior middle line during exertion [ 8 , 10 ]; anogenital size (AGD): the distance between the external genitalia from the anterior part of the clitoris to the anus and PB+GH [ 11 ]. Data collected through questionnaires were analyzed using SPSS-21.…”
Section: Methodsmentioning
confidence: 99%